2002
DOI: 10.1097/00000539-200204000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Does Indocyanine Green Accurately Measure Plasma Volume Early After Cardiac Surgery?

Abstract: Overestimation of indocyanine green-derived plasma volume can occur in the presence of generalized capillary protein leakage. This overestimation was examined early after cardiac surgery by using the simultaneous measurement of the initial distribution volume of glucose. We suggest that overestimation of the traditional dye dilution method is negligible, but apparent over- or underestimation of pulse dye densitometry-derived plasma volume cannot be negligible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 18 publications
3
21
0
Order By: Relevance
“…For the plasma method (14,15,20,29), only one single venous cannula, inserted into a cubital vein, is needed. After calibration of the system (measurement of the specific extinction in two 5-ml samples of the patient's plasma containing ICG at 2 artificially generated concentrations), the dye (0.25 mg ICG/kg body wt) is injected into the patient's circulation at t 0 .…”
Section: Determining Icg Concentrationmentioning
confidence: 99%
See 2 more Smart Citations
“…For the plasma method (14,15,20,29), only one single venous cannula, inserted into a cubital vein, is needed. After calibration of the system (measurement of the specific extinction in two 5-ml samples of the patient's plasma containing ICG at 2 artificially generated concentrations), the dye (0.25 mg ICG/kg body wt) is injected into the patient's circulation at t 0 .…”
Section: Determining Icg Concentrationmentioning
confidence: 99%
“…The point is to correctly interpret this value to establish the "real" PV, and this is obviously a serious problem for some investigators (20,23,29): PV derived via ICG-DT was, e.g., "checked for correctness" by calculating RCV from PV and Hct LV and expecting this RCV derived from ICG (RCV ICG ) to be constant in the absence of any bleeding or transfusion if the ICG-DT was consistent. In other cases, PV derived from ICG-DT (PV ICG ) was expected, as a proof for consistency of the method, to be constant before and after an intervention (e.g., induction of general anesthesia or volume loading).…”
Section: From Dsicg To Pv: Physiological Background Of a Technical Mementioning
confidence: 99%
See 1 more Smart Citation
“…Indocyanine green (ICG) is a relatively non−toxic dye [4] which is applied as an optical marker for liver func− tion testing [5][6][7] in ophthalmology [8] and for assessment of hemodynamic parameters [9][10][11]. In experiments carried out on animals it was also shown that the ICG monitoring may allow for evaluation of cerebral blood volume [12].…”
Section: Introductionmentioning
confidence: 99%
“…1). ICG was chosen because of widespread use in medical testing [17][18][19] and growing use as a contrast agent in optical tomography [20][21][22]. We speculated that the long wavelength absorption and emission wavelengths of ICG may minimize quenching due to the gold absorption while still increasing the photostability.…”
Section: Introductionmentioning
confidence: 99%